Staphylococcus aureus uses a GGDEF protein to recruit diacylglycerol kinase to the membrane for lipid recycling - Aaron Mychack; Dwayne Evans; Tarah Gilles; Michael J. James; Suzanne Walker (Proceedings of the National Academy of Sciences, 2025)
Staphylococcus aureus is a Gram-positive pathogen responsible for numerous antibiotic-resistant infections. Identifying vulnerabilities in S. aureus is crucial for developing new antibiotics to treat these infections. With this in mind, we probed the function of GdpS, a conserved Staphylococcal membrane protein containing a cytoplasmic GGDEF domain. These domains are canonically involved in cyclic-di-GMP signaling processes, but S. aureus is not known to make cyclic-di-GMP. Using a transposon screen, we found that loss of GdpS is lethal when combined with disruption in synthesis of the glycolipid anchor of a cell surface polymer called lipoteichoic acid (LTA) or with deletion of genes important in cell division. Taking advantage of a small molecule that inhibits LTA glycolipid anchor synthesis, we selected for suppressors of Δ gdpS lethality. The most prevalent suppressors were hypermorphic alleles of dgkB , which encodes a soluble diacylglycerol (DAG) kinase required to recycle DAG to phosphatidylglycerol. By following up on these suppressors, we found that the GGDEF domain of GdpS interacts directly with DgkB, orienting its active site at the membrane to promote DAG recycling. DAG kinase hypermorphs also suppressed the lethality caused by combined loss of gdpS and cell division factors, highlighting the importance of lipid homeostasis for cell division. GdpS’ positive regulation of DAG kinase function was dependent on the GGDEF domain but not its catalytic residues. As the sole conserved GGDEF-domain protein in Staphylococci, GdpS promotes an enzymatic process independent of cyclic-di-GMP signaling, revealing a new function for the ubiquitously conserved GGDEF domain.